Shifting mindsets from conference to (un)conference: A collaborative reflective perspective on conceptual disruption - Pather, Subethra; Govender, Rosaline; Scholtz, Desiree (Critical Studies in Teaching and Learning, 2024)
The move from the traditional academic conference format to a loosely defined format of unconference can be contentious and spark a robust debate on the conceptual disruption of conferencing. As part of HELTASA’s strategic plan of re-structuring and re-imagining its vision and purpose, it initiated a new way of conferencing; participant-driven and participant-focused. Through self-reflective written narratives, this paper explores three academic development practitioners’ experiences in planning and reflecting on the HELTASA’s (un)conference. We share our accounts of (un)conference as a conceptual disruption to the traditional conference format, concepts, and ways of doing and being. Qualitative data were collected from the three written narratives through a collective descriptive autoethnography research design and methodology. The insights collected are applied to the Conceptual Disruption Framework which proposes a tripartite framework for conceptual disruption, which distinguishes conceptual disruptions occurring at three levels (individual concepts, clusters of concepts, conceptual schemes), taking on two forms (conceptual gaps, conceptual conflicts), and leading to three distinct levels of severity (mild, moderate, severe). Using this framework, we describe our personal thoughts and perspectives in engaging with the novel approach of (un)conferencing. We probe into the potential of collaborative reflection to gain deeper insights and understanding of our shift from a traditional academic conference to a HELTASA (un)conference. We explore the discomfort, displacement, and learnings of the intentional disruption of our conceptual understanding of (un)conference practices. This paper highlights our shifting mindsets as we reflect and interrogate our thoughts and perspectives on the conceptual framing of (un)conferencing. The analysis of the data reveals that the engagement in the conceptual disruption of (un)conferencing together with the engagement with the concept planning and event provided the environment and atmosphere where the team appreciated brainstorming conceptual understandings, self-reflecting, and exploring different perspectives. This study provides empirical evidence of strength in collaboration, the building of conceptual disruption as a community of practice and possibility of (un)conferencing being a shape-shifter in higher education. At an interpersonal level, the process allowed us to self-interrogate the conceptual disruption, unpacking our thoughts and shaping our own thinking. The paper asserts that shifting mindsets from conference to (un)conference, involves conceptual disruption which is a messy process and requires a level of trust, openness, adaptability amongst all members of the organising team.